제지폐수열 회수로부터 에너지 절감 및 온실가스 감축에 관한 실증연구 - 김도훈; 강성효; 김찬호; 이헌영; 조일형 (한국수처리학회지, 25(1), 2017)
Papermaking wastewater contains significant quantities of thermal energy. Consequently, heat recovery in papermaking wastewater can provide paper process with an additional source of renewable energy as steam. Wastewater heat recovery system is achieved by taking wasted energy in wastewater through specially designed shell & tube heat exchangers with a multi pre-filtration system (the so-called ENSAVER system). The feasibility study presented in terms of applications and performance assessments including temperature difference by heat transfer & exchange, energy saving, environmental and economic aspects. The temperature difference between the inlet and outlet wastewater was 6.73±1.83℃, while the temperature difference between the inlet and outlet clean water was 8.68±2.52℃. The temperature and heat efficiencies were 68.6±16.8% and 86±2.1%, respectively. Especially, the obtained heat efficiency was high compared to commercial heat recovery system in which the heat efficiency of < 60% was achieved in industrial wastewater. It was shown that the proposed heat recovery system reduced natural gas costs by 400±112 million won/y and greenhouse gas emissions by 1,069±299 t/y of CO2. It could be sure to provide energy saving by employing a wastewater heat recovery system (ENSAVER). Using simulations with a regression model, a quantitative relationship between various variables (X1: Inflow rate (m3/h) in wastewater, X2: Inlet wastewater temperature (℃), X3: Outlet wastewater temperature (℃), X4: Inlet clean temperature (℃), and X5: Outlet clean water temperature (℃) and response Y (Reducing the amount of CO2 GHG emission (tCO2/y)) was established. It is observed that there are tendencies in the linear regression fit, and the model explains the experimental range studied adequately. The fitted regression equation showed a good fit (R2=99.56%) of the model. KCI Citation Count: 0